How Do Children "Think outside the Box"? Fluid Intelligence and Divergent Thinking: A Moderated Mediation Study of Field Dependent-Independent Cognitive Style and Gender - Marco Giancola; Massimiliano Palmiero; Maria Chiara Pino; Marta Sannino; Simonetta D'Amico (MDPI AG, 2024)
The interplay between fluid intelligence (Gf) and divergent thinking (DT) has widely characterized current research in the psychology of creativity. Nevertheless, the evidence on the main factors involved in this association during childhood remains a matter of debate. Present research has addressed the interplay between Gf and DT, exploring the mediating role of a field dependent-independent cognitive style (FDI) and the moderating effect of gender in 101 children (Mage = 8.02; SDage = 1.43). Participants carried out Raven's Colored Progressive Matrices, the Children Embedded Figure Test, and the Alternative Uses Task. The results revealed the mediating effect of FDI in the association between Gf and DT, providing evidence that this cognitive style represents a function of controlled mental processes underpinned by Gf, which are useful to thinking divergently. In addition, the findings reported that the interplay between FDI and DT was moderated by gender, suggesting that the impact of FDI on DT was stronger among boys. Through a multidimensional approach, these current research findings provide further insight into the primary children's factors involved in the ability to find alternative solutions and think divergently.